Microbial Biopolymers Trends in Synthesis, Modification, and Applications - Kant Bhatia, Shashi (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
"Microbial Biopolymers: Trends in Synthesis, Modification and Applications" is a comprehensive reprint that explores the latest research and innovations in the field of biopolymers. The reprint covers the production and functionalization of two key types of microbial biopolymers: polyhydroxyalkanoates (PHAs) and exopolysaccharides (EPSs). With contributions from leading experts in the field, the reprint provides a thorough overview of the production processes, chemical and physical properties, and applications of these biopolymers. The reprint is an essential resource for researchers, engineers, and industry professionals interested in developing sustainable and eco-friendly alternatives to conventional plastics and materials.